PENENTU BESARAN TRANSAKSI PIHAK BERELASI: TATA KELOLA, TINGKAT PENGUNGKAPAN, DAN STRUKTUR KEPEMILIKAN - Utama, Cynthia Afriani (UI Scholars Hub, 2015)
Indonesian firms are characterized by conglomeration that tends to conduct related party transaction (RPT). Extant academic literature provides two competing views on RPTs: the efficient transaction hypothesis and the conflict of interest hypothesis. The purpose of this study is to investigate RPT from the point of view of the conflict of interest hypothesis. Specifically, this study examines the size of RPT which is performed by majority shareholders to expropriate minority shareholders. The size of RPT measures the direct influence of RPT on shareholders’ wealth. In this study, the size of RPT is measured by RPT transactions of assets plus liabilities (RPTAL) and sales plus expenses (RPTSE) relative to book value of equity. Furthermore, this study investigates whether RPTAL and RPSE are determined by CG practices, disclosure of RPT, and ownership structure. This study cannot find the influence of CG on size of RPTAL and RPTSE. The results of the study also show that only disclosure of RPT and ownership structure that have positive impact on size of RPTSE. Disclosure of RPT increases more efficient RPTSE than abusive RPTSE. This study find that the relationship between the disclosure and RPTAL is insignificant as efficient RPTAL does not dominate abusive RPTAL, while concentrated ownership has a positive impact on abusive RPTSE.